Modeling decisions for artificial intelligence : 19th International Conference, MDAI 2022, Sant Cugat, Spain, August 30-September 2, 2022, proceedings - MDAI (Conference) (19th : 2022 : San Cugat del Vallés, Spain); Torra, Vicenç; 成川, 康男 (Lecture notes in computer science. Lecture notes in artificial intelligence, 2022)
This book constitutes the refereed proceedings of the 19th International Conference on Modeling Decisions for Artificial Intelligence, MDAI 2022, held in Sant Cugat, Spain, during August - September 2022.The 16 papers presented in this volume were carefully reviewed and selected from 41 submissions. The papers discuss different facets of decision processes in a broad sense and present research in data science, machine learning, data privacy, aggregation functions, human decision-making, graphs and social networks, and recommendation and search. They were organized in topical sections as follows: Decision making and uncertainty; Data privacy; Machine Learning and data science.